ANALYSIS OF THE SEVENTH GRADE STUDENTS’ DIFFICULTIES FACTOR IN READING COMPREHENSION AT SMPN 1 CAMPURDARAT - Lubis, Suci Nuraini; Dwinata, Erna (Fakultas Keguruan dan Ilmu Pendidikan Universitas Pakuan, 2024)
Reading is important in learning English. The ability to reading comprehension is an ability that is naturally not owned by a student. In practice, this process is seen as complex, so it is not impossible that learning in reading comprehension obstacles and problems when learning implement it. The aim of this research is to find out the causal factors of students' reading comprehension difficulties on descriptive text at the seventh grade of SMPN 1 Campurdarat. This research is a descriptive qualitative research. The subject of the research is seventh grade students of SMPN 1 Campurdarat in Academic Year 2022/2023. The techniques of collecting the data are interview and test. Data analyzing include data reduction, data display and drawing conclusions or verification, the researcher arranging the information described in order to draw conclusion. The result of the research shows that the factor of causing the students difficulties found in comprehending English reading text there are difficulty in understanding long sentence in the text, difficulty in using reading strategies, difficulty in Concentration, learner's background, house environment and school environment.